PENGELOLAAN PAJAK DAERAH DAN RETRBUSI DAERAH KOTA CILEGON - Indah Indah; Ulfi Jefri; Amyati Amyati (Jurnal Bina Bangsa Ekonomika, 2023)
Local taxes and local levies have significant potential as a major source of local revenue. To realize effective regional autonomy, competent financial management is needed so that the targets set can be achieved concretely. This can be achieved by setting targets and measuring real achievements. The purpose of this study is to understand the level of effectiveness, contribution, and growth rate of local taxes and levies in Cilegon City from 2017 to 2021. This research applies qualitative descriptive methods by utilizing primary and secondary data sources. Primary data was obtained through direct interviews with related agencies, while secondary data was obtained from the Cilegon City Budget Realization Report from 2017 to 2021 obtained from the Cilegon City BPKAD. The results showed that the level of effectiveness, contribution and growth rate of regional taxes and levies in Cilegon City in 2017-2021 varied greatly. The effectiveness rate of local taxes and levies can be said to be effective with the effectiveness value of local taxes of 94.05% and the effectiveness value of regional levies of 95.09%. The local tax contribution rate can be said to be very good with a contribution value of 75.33%. The contribution rate of the regional levy can be said to be very less with a contribution value of 2.71%. The growth rate of local taxes and regional levies is classified as unsuccessful with the value of the growth rate of local taxes of 1.89% and the value of the growth rate of regional levies of -0.98%. It can be concluded that local tax revenues and local levies have reached an adequate level of effectiveness. The contribution of local tax revenue is considered very good, while the contribution of regional levy revenue is considered very lacking. However, the growth rate of local taxes and local levies did not achieve the expected results